Pengelolaan Pembelajaran BermuatanNilai-Nilai Karakter Pada Kelas BawahDi SDII Al Abidin Surakarta - , Shodiqin, Dr. Sabar Narimo, MM, M.Pd, Dr. Maryadi, MA (2017)
This study aims to (1) Describe the process of lesson planning laden character values in the lower classes in SDII Al Abidin Surakarta, (2) Describe the process of learning implementation charged character values in the class in SDII Al Abidin Surakarta, (3) Describe the evaluation curriculum charged character values in the lower classes in SDII Al Abidin Surakarta. This study uses qualitative research conducted in SDII Al Abidin Surakarta. The main subjects in this study were principals and teachers. Data collection techniques used in this study is observation, interview and documentation. Data analysis techniques in this study using a model of analysis, data collection, data reduction and data presentation and conclusion. The validity of the data in penilitan by triangulation data. The results of this study show that: (1) Planning instructional charged character values developed through a workshop at the beginning of the semester results in a learning device in the form of the Syllabus, Annual Program, Program Semester, RPP and planting program code (2) Implementation of the learningcharged character values held by RPP are made with regard to objectives, materials, methods, media and ratings as well as habituation cultivation of character to character values achieved (3) evaluation of the curriculum implemented by principals through supervision activities to determine the achievement of the curriculum as well as a reference in the follow-up repairs.